Water quality assessment of the Banong River receiving effluent from Sleman Public Hospital - Muchsin Maulana; Didik Setiawan; Wonder N. Dlamini (International Journal of Public Health Science (IJPHS), 2026)
Hospital effluent has the potential to release both chemical substances and pathogenic microorganisms into surrounding water bodies, creating hazards for the environment and human health. There is a scarcity of studies in Indonesia that assess the impact of hospital wastewater on river ecosystems using benchmark regulations. This study measured the quality of wastewater at a point 50 meters before discharge and 50 meters after the wastewater treatment plant by analyzing six main parameters of temperature, potential of hydrogen (pH), Biochemical oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), and total suspended solids (TSS), then compared with the water quality standards according to the Regulation of the Governor of the Special Region of Yogyakarta No. 20/2008. This study found that although temperature and pH remained within acceptable ranges, higher BOD, COD, and TDS levels downstream indicated that hospital wastewater was adding to the river's organic and chemical pollution. Improved wastewater treatment processes and consistent monitoring are essential to protect ecosystem integrity and public health.